Three-Dimensional Visualization of Defects Formed during the Synthesis of Metal-Organic Frameworks: A Fluorescence Microscopy Study - Ameloot, Rob; Vermoortele, Frederik; Hofkens, Johan; De Schryver, Frans C.; De Vos, Dirk E.; Roeffaers, Maarten B. J. (Angewandte Chemie International Edition, 2013)
Imperfections in the spotlight: Fluorescence microscopy was used to detect defects in metal–organic frameworks formed during synthesis. In contrast to currently available techniques, confocal fluorescence microscopy offers the advantage of three‐dimensional imaging at the single‐crystal level combined with the sensitivity required to study the start of defect formation.